EVALUATION OF ANIMAL HEALTH SYSTEMS: DEMAND FOR SERVICES IN THE AUTONOMOUS CITY OF BUENOS AIRES - Martínez, María Cecilia (2013)
The analysis of the vision of the community in line with the socio-cultural needs is proposed in order to assess how influence decisions on the tenure of pets and on the demand for animal health services. The aim of this study was to analyze the current demand for animal health services in the Autonomous City of Buenos Aires. The study used the model of social survey in a group of people who attended the services of the Institute of Zoonosis Dr. Louis Pasteur (IZLP) and a comparison group who performed activities in the city that were unrelated to animal health. There was no difference in the demographic characteristics of the studied groups. Requested veterinary care in the past year was similar in both groups, but differing on the type of services required. Both groups considered as satisfactory the health services but felt the need to incorporate or enhance health actions, which in many cases, were already running.